2013
DOI: 10.1038/ncomms3360
|View full text |Cite
|
Sign up to set email alerts
|

High charge-carrier mobility enables exploitation of carrier multiplication in quantum-dot films

Abstract: Carrier multiplication, the generation of multiple electron–hole pairs by a single photon, is of great interest for solar cells as it may enhance their photocurrent. This process has been shown to occur efficiently in colloidal quantum dots, however, harvesting of the generated multiple charges has proved difficult. Here we show that by tuning the charge-carrier mobility in quantum-dot films, carrier multiplication can be optimized and may show an efficiency as high as in colloidal dispersion. Our results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 38 publications
7
97
0
Order By: Relevance
“…Interestingly, PbSe nanorods in the solid state show a sharper increase in QY with photon energy compared to equivalent nanorods in solution despite the fact that device IQEs are typically reduced by Auger recombination competing with charge separation and by regular device recombination losses (see Figure 5). Similar observations have been reported for spherical QDs where the MEG yield of particles in film and solution have been examined via microwave conductivity measurements [117]. Possible explanations for this phenomenon range from the formation of interparticle QD band structures in the solid state [117] to potential trap-assisted MEG mechanisms [118].…”
Section: Tuning the Shape Of The Qdsupporting
confidence: 56%
See 2 more Smart Citations
“…Interestingly, PbSe nanorods in the solid state show a sharper increase in QY with photon energy compared to equivalent nanorods in solution despite the fact that device IQEs are typically reduced by Auger recombination competing with charge separation and by regular device recombination losses (see Figure 5). Similar observations have been reported for spherical QDs where the MEG yield of particles in film and solution have been examined via microwave conductivity measurements [117]. Possible explanations for this phenomenon range from the formation of interparticle QD band structures in the solid state [117] to potential trap-assisted MEG mechanisms [118].…”
Section: Tuning the Shape Of The Qdsupporting
confidence: 56%
“…Similar observations have been reported for spherical QDs where the MEG yield of particles in film and solution have been examined via microwave conductivity measurements [117]. Possible explanations for this phenomenon range from the formation of interparticle QD band structures in the solid state [117] to potential trap-assisted MEG mechanisms [118].…”
Section: Tuning the Shape Of The Qdsupporting
confidence: 56%
See 1 more Smart Citation
“…. 93 With both ptype and n-type PbS NC availability along with their tunable bandgap, there remains an intresting opportunity to realise all PbS p-n heterojunction photodiodes.…”
Section: Discussionmentioning
confidence: 99%
“…2) and EQE spectra (Fig. 1d) that do not show red-shift and broadening as signatures of increased electronic coupling and loss of quantum confinement 26,27 . This is in agreement with a previous report by Gao et al 28 , in which annealing of EDT-treated PbS films was reported to suppress deep traps in the temperature regime investigated herein without loss of quantum confinement.…”
Section: Oh -Suppression and Improved Passivation Via Thermal Annealingmentioning
confidence: 99%